USE OF THE AUTOMATION EQUIPMENT OF IBA FIRM FOR DIAGNOSTICS OF MALFUNCTIONS OF THE EQUIPMENT IN PIPE-ROLLING PRODUCTION - A. V. Chubenko (Литьë и металлургия)
Experience of utilization of IBA automation equipment for diagnostics of malfunctions of the equipment is given. The analysis of advantages of utilization of diagnostic aids of malfunctions of IBA firm in the BSW pipe-rolling shop is made.